Threonine(175), a novel pathological phosphorylation site on tau protein linked to multiple tauopathies - Moszczynski, Alexander J. (Acta Neuropathol Commun, 2017)
Microtubule associated protein tau (tau) deposition is associated with a spectrum of neurodegenerative diseases collectively termed tauopathies. We have previously shown that amyotrophic lateral sclerosis (ALS) with cognitive impairment (ALSci) is associated with tau phosphorylation at Thr(175) and that this leads to activation of GSK3β which then induces phosphorylation at tau Thr(231). This latter step leads to dissociation of tau from microtubules and pathological tau fibril formation. To determine the extent to which this pathway is unique to ALS, we have investigated the expression of pThr(175) tau and pThr(231) tau across a range of frontotemporal degenerations. Representative sections from the superior frontal cortex, anterior cingulate cortex (ACC), amygdala, hippocampal formation, basal ganglia, and substantia nigra were selected from neuropathologically confirmed cases of Alzheimer’s disease (AD; n = 3), vascular dementia (n = 2), frontotemporal lobar degeneration (FTLD; n = 4), ALS (n = 5), ALSci (n = 6), Parkinson’s disease (PD; n = 5), corticobasal degeneration (CBD; n = 2), diffuse Lewy body dementia (DLBD; n = 2), mixed DLBD (n = 3), multisystem atrophy (MSA; n = 6) and Pick’s disease (n = 1) and three neuropathologically-normal control groups aged 50–60 (n = 6), 60–70 (n = 6) and 70–80 (n = 8). Sections were examined using a panel of phospho-tau antibodies (pSer(208,210), pThr(217), pThr(175), pThr(231), pSer(202) and T22 (oligomeric tau)). Across diseases, phospho-tau load was most prominent in layers II/III of the entorhinal cortex, amygdala and hippocampus. This is in contrast to the preferential deposition of phospho-tau in the ACC and frontal cortex in ALSci. Controls showed pThr(175) tau expression only in the 7(th) decade of life and only in the presence of tau pathology and tau oligomers. With the exception of DLBD, we observed pThr(175) co-localizing with pThr(231) in the same cell populations as T22 positivity. This suggests that this pathway may be a common mechanism of toxicity across the tauopathies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40478-016-0406-4) contains supplementary material, which is available to authorized users.